Noetherian module matrix over commutative ring - Abdurrazzaq, Achmad author (Institute of Engineering Mathematics, Universiti Malaysia Perlis, 2017)
The objectives of this research are ; to investigate the Noetherian properties related group, ring, and module ; to determine the algebraic structures for entries of the matrix ; to validate that every axioms on module theory fulfilled for set of matrix ; to investigate and propose some conditions related Noetherian module for set of matrix.